Translation Techniques Employed in Indonesian Subtitles of The Children’s Film "Stuart Little" on Netflix - Eliansy, Ennie (Journal of English Education, Literature and Linguistics, 2025)
This study analyzes the Indonesian subtitles of the movie Stuart Little (1999) on Netflix, focusing on how the subtitles are adapted for Indonesian audiences, particularly young viewers and this study utilized a qualitative approach. The study identifies five main techniques used in subtitle translation: expansion, cultural adaptation, simplification, localization, and domestication. Expansion involves adding details to clarify meaning, while cultural adaptation modifies culturally specific references to align with the cultural norms of the target audience. Simplification reduces linguistic complexity to make the content easier for viewers to understand, and localization adjusts expressions, humor, and idioms to align with local language usage. Domestication transforms foreign elements into forms more relatable to the target audience. These techniques help to enhance comprehension and ensure cultural relevance, making the movie more accessible and enjoyable for Indonesian viewers. The findings highlight the importance of tailoring subtitles to meet the cultural and linguistic needs of the audience, particularly in major media aimed at younger viewers.